Electromagnetic-Based Microfluidic Sensor Applications. Issue 9 (4th August 2017) - Bakir, Mehmet
Abstract : In this study, Metamaterial Based Microfluidic Sensor (MBMS), which is designed by utilising a Split Ring Resonator (SRR) along with a patch has been employed to reveal the three different types of sensor applications by experimentally and numerically. These applications include purity demonstration of methanol, ethanol and acetone, different material sensing which is illustrated by poly ethylene glycol (PEG 300, PEG400) and temperature sensor application which is new in the current literature and proven by utilising pure ammonia solution. In the first step of the validation, these materials' complex permittivity values were measured using an Agilent 85070E dielectric probe kit between 4 GHz and 6 GHz. Following this, a numerical simulation test was conducted by applying a FIT-based simulation programme. Finally, in order to verify the numerical simulation study, a proposed design has been manufactured prior to carrying out an experimental study on all of the applications. To support the simulation and experimental results, theoretical study carried out and obtained results were compared with similar studies. Both the numerical and experimental results reveal that the proposed Microfluidic sensor, which is based on a change in the complex permittivity, can be configured and applied to other sensing tools.